Explorando bioativos da Caatinga: extrato hidroetanólico de Apodanthera glaziovii COGN. (cucurbitaceae) rico em saponinas demonstra forte atividade anti-inflamatória - Andrade, Maria Lorena de Oliveira (2024)
Medicinal plants are recognized for providing various health benefits, as reported for several species of the cucurbitaceae family, such as watermelon, melon and pumpkin. Belonging to this family, the species Apodanthera glaziovii has aroused interest in phytochemical and pharmacological studies due to the scarcity of research into its therapeutic potential and chemical constituents. In this study, qualitative and quantitative approaches were used to identify the secondary metabolites present in the species in question. In addition, the compounds were analyzed and isolated using High Performance Liquid Chromatography coupled with Diode Array Detection (HPLC-DAD). To assess the antimicrobial activity of the freeze-dried hydroethanolic extract (70%) of A. glaziovii (EHL-Ag), the microdilution plate test was used, both for bacteria and fungi. With regard to toxicity, methods were used to assess hemolytic activity in human erythrocytes, as well as the in vivo acute toxicity test. In addition, a genotoxicity test was carried out, determining the number of micronucleated polychromatic erythrocytes (MNPCE) in mice. To investigate anti-inflammatory activity, carrageenaninduced paw edema, peritonitis and air pocket tests were used. The results showed that saponins are the predominant metabolites in this species. Chromatographic analysis identified characteristic wavelengths of cayponosides (nor-cucurbitacins), leading to the isolation of a compound known as Cayponoside D2. Although the Apodanthera glaziovii extract did not demonstrate antimicrobial activity for the microorganisms tested, hemolytic toxicity tests indicated a low hemolytic potential, with the highest concentration tested of 2000 μg /mL corresponding to only 4.80% hemolysis. In the acute toxicity test on mice in vivo, the extract showed signs of toxicity in biochemical and hematological parameters at a dose of 2,000 mg/kg. On the other hand, the results of the anti-inflammatory activity were promising: the extract significantly reduced paw edema by 55%, neutrophil influx by 68% and leukocyte influx by 62% in peritonitis, as well as reducing neutrophil influx by 70% in the air pocket test, all at a dose of 100 mg/kg. These findings suggest that Apodanthera glaziovii has anti-inflammatory potential, highlighting the importance of research into new therapeutic agents in medicinal plants.